2022
DOI: 10.3390/coatings12010074
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of the Superhydrophobic State to Protect Magnesium Alloy against Corrosion

Abstract: We describe the technologically simple route for the fabrication of the superhydrophobic coatings on top of wrought magnesium alloy MA8 based on nanosecond laser processing followed by the chemical vapor deposition of fluorosilane. The chemical and phase composition, surface morphologies, and variation of the coating wettability during prolonged contact with 0.5 NaCl solution or with salt aerosol were characterized using X-ray diffraction, FT-IR spectroscopy, scanning electron microscopy measurements, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The antibacterial rates of S. aureus in SHL-150 µm and SHB-150 µm were 8.01% and 82.05%, respectively. The big difference in antibacterial rates in these specimens showed that the laser-chemical surface treatment induced superhydrophobicity and improved the antibacterial performance of Mg alloy significantly [36,37]. Equation ( 1) was used to calculate the antibacterial rate of the laser-structured and laser-chemical-treated specimens based on China's standard GB/T 2591 [56], as shown in Figure 11.…”
Section: Antibacterial Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial rates of S. aureus in SHL-150 µm and SHB-150 µm were 8.01% and 82.05%, respectively. The big difference in antibacterial rates in these specimens showed that the laser-chemical surface treatment induced superhydrophobicity and improved the antibacterial performance of Mg alloy significantly [36,37]. Equation ( 1) was used to calculate the antibacterial rate of the laser-structured and laser-chemical-treated specimens based on China's standard GB/T 2591 [56], as shown in Figure 11.…”
Section: Antibacterial Propertymentioning
confidence: 99%
“…The laser-chemical-treated surface of superhydrophobic Mg AZ91D showed excellent corrosion resistance. Emelyanenko et al [36] processed superhydrophobic Mg MA8 using a nanosecond laser and CVD with fluorosilane. The corrosion current of the processed Mg MA8 was drastically reduced when it was compared with that of the polished sample.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous part, we summarize the preparation strategy and protection mechanism of superhydrophobic coatings to abate the corrosion behavior of Mg alloys ( Table 1 ) [ 7 , 33 , 42 , 52 , 57 , 68 , 70 , 72 , 73 , 74 , 75 , 76 , 77 ], which is helpful for researchers to develop superhydrophobic film with enhanced anti-corrosion characteristics on the Mg alloy. The advantages and disadvantages of various preparation technologies were compared.…”
Section: Superhydrophobic Coatingsmentioning
confidence: 99%
“…While superhydrophobic coatings with great water repellency can provide outstanding barrier protection. The fabrication of hydrophobic and superhydrophobic coatings has emerged as a novel method to prevent metals corrosion because the as-formed air cushion at the solid–liquid interface acts as a physical barrier. This can effectively reduce the contact area between the two, preventing or slowing the intrusion of the corrosive medium through the coating .…”
Section: Introductionmentioning
confidence: 99%